Brazilian feminisms in global spaces: Beijing and Beijing+20 - Sardenberg, Cecília Maria Bacellar (2015)
Within the last decades, feminist movements in Brazil have advanced significantly beyond borders,gaining increasing recognition in global spaces, UN ones in particular, for positively influencing Brazil’s official position. Unsurprisingly, Brazil has served four terms in the Commission on the Status of Women (CSW) and, in the eyes of more progressive delegations, is a much needed presence to ensure no lost ground on what has been achieved in previous conferences. However, the actual presence of Brazilian feminist activists in the delegations and the NGO Forums has dwindled considerably. What have been the strategies and mechanisms at play in maintaining a radical vein in our official position? Can it be sustained without the more active involvement of feminist activists – say, throughout Brazil’s new role as president of the 60th CSW session? These are some of the issues I address in this article, sharing the views of activists present at those events.